Investigation of Perforated Tube Configuration Effect on the Performance of Exhaust Mufflers with Mean Flow Based on Three-Dimensional Analysis - MOHAMAD, Barhm; KAROLY, Jalics; ZELENTSOV, Andrei; AMROUNE, Salah (Archives of Acoustics, 2021)
Using perforated tube in exhaust mufflers is known to improve transmission loss (TL) by improving their sound pressure level (SPL) at the orifice. The perforated tube should affect the muffler performance analogous to a shell-and-tube heat exchanger. To the authors’ knowledge, there are few previous assessments reported in literature of the effects that the perforated tube configuration has on acoustic response and pressure drop predicted. The effects of (i) the perforated tube length, (ii) the diameter of tube holes, and (iii) flow through perforated tube were investigated. To assess the perforated tube effect on flow, the SOLIDWORKS 2017 based on Computational Fluid Dynamics (CFD) tool was utilized using real walls approach model with a surface roughness of 0.5 micrometres (AISI 316 cold rolled stainless steel sheet (ss) Ra = 0:5 μm). Perforated tube was found to cause back pressure which may increase SPL about 10%.